Establishment and Bioreactor Cultivation of Morinda Elliptica Cell Cultures for the Production of Anthraquinones - Abdullah, Mohd Azmuddin (1999)
Morinda elliptica (Rubiaceae) cell suspension cultures were established in shake flask and bioreactor systems for the production of anthraquinones (AQ). To improve AQ productivity at shake flask level, manipulations of media components such as carbon, nitrogen, phosphate and myo-inositol; and cultural conditions such as incubation temperature, light intensity, culture and inoculum age, were made. At bioreactor level, the study was aimed at finding the best bioreactor operation with minimmn foaming and wall-growth problem. Several strategies such as mode of aeration, number of impellers, paddle orientation, antifoam addition and medium fonnulations, were applied. Murashige and Skoog's basal medium was found to be the best medium in enhancing both cell growth and AQ production. By manipUlation of sucrose concentration, hormone combination and concentration, culture age and inoculum age, the type of medium formulation used to grow inoculum, incubation temperature and light intensity, three types of media were formulated - maintenance medium (M), growth medium (G) and production medium (P). The toxic effects of nitrogen were shown not a result of the individual effect of nitrogen toxicity per se but of both individual and collective effects of NR₄⁺ and N0₃⁻ levels, in consonance with the level of sucrose and the medium formulation used. Reduction in pH for cultures grown in medium containing high concentration of NR₄⁺ was another contributing factor for ammonium toxicity. Phosphate had little influence on cell growth and AQ production though its absence could suppress growth completely. The phosphate toxicity could also occur depending on sucrose level and medium formulation. Myoinositol was not an absolute requirement in M elliptica cell suspension culture. The growth of cell suspension cultures of M elliptica in G and P media were sigmoidal. The AQ yields in P medium, of 2.9 and 4.5 gl⁻₁ with corresponding overall productivity of 0.14 and 0.21 gl⁻₁ dl⁻₁ , under illumination and in the dark, respectively, were among the highest amount of secondary metabolites and productivities by plant cell suspension cultures. The formation of AQ displayed a non-growth associated characteristic. High sucrose, glucose and fructose concentration over the period of two weeks in P medium was suggested to cause osmotic pressure on the cells which hindered rapid growth, leading to higher accumulation of AQ. With increasing culture age to 36 month-old, the doubling time was increased by 30% to 1.5 days; and 100% to l .6 days, in M and P medium, respectively. The maximum cell concentration in LP(36) was however 35% lower than LP(l8) while the AQ yield dropped sharply from 2.92 g l⁻₁ to a mere 0.55 g l⁻₁ . The spent medium was observed more yellowish in LP(36) indicating that AQ was no longer retained in the cell vacuole but released into the medium. The faster rate of sucrose hydrolysis and uptake rate of glucose and fructose in LP(36) may have reduced the osmotic pressure in the medium which allows rapid cell growth and diffusion of AQ.